PENGARUH PENGETAHUAN TERHADAP PERILAKU PETANI RUMPUT LAUT - -, Fatmawati (Jurnal Ilmiah Ecosystem, 2018)
This study aims to determine the effect of environmental knowledge and knowledge of postharvest seaweed on farmer's behavior, both individually and jointly. Correlational research survey method, a total sample of 100 seaweed farmers, was chosen by a simple random method. Seaweed farmer's behavior as a dependent variable, as well as environmental knowledge and postharvest knowledge as independent variables. Data were analyzed by simple regression methods and multiple regression. The results found that environmental knowledge and knowledge of postharvest seaweed, positively and significantly affect the behavior of farmers in seaweed postharvest management, both individually and jointly.